Musicians and Musical Instruments in Roman and Early Byzantine Mosaics of Eretz Israel: Sources, Precursors and Significance - Mucznik, Sonia (Gerión. Revista de Historia Antigua, 2012)
Musical instruments and musicians depicted on several Roman and Byzantine mosaics of Eretz Israel (Land of Israel) figure in various scenes, some having a sacred context and others an earthly one. The meaning of each instrument is determined by the character of the scenes, and also by the location in which they appear. In this article I studied the ancient local musical culture, the precursors, as well as literary and philosophical sources in order to clarify the role and significance of the images. The archaeological findings were examined with the aim to define the accessible iconographical sources and to establish the genre and the context in which the motifs are presented.